The Bogolubov generating functional method in statistical physics and “collective” variables transform within the grand canonical ensemble - Bogolubov (jr.), N.N.; Prykarpatsky, A.K. (Інститут математики НАН України, 2007)
We show that the Bogolubov generating functional method is a very effective tool for studying distribution functions of both equilibrium and nonequilibrium states of classical many-particle dynamical systems. In some cases the Bogolubov generating functionals can be represented by means of infinite Ursell –Mayer diagram expansions, whose convergence holds under some additional constraints on the statistical system under consideration. The classical Bogolubov idea to use the Wigner density operator transformation for studying the nonequilibrium distribution functions is developed, a new analytic nonstationary solution to the classical Bogolubov evolution functional equation is constructed.